Long-term survival after self-expanding metallic stent or stoma decompression as bridge to surgery in acute malignant large bowel obstruction. Issue 2 (21st April 2021) - Axmarker, T; Leffler, M; Lepsenyi, M; Thorlacius, H; Syk, I
Abstract: Aim: Self-expanding metallic stents (SEMS) as bridge to surgery have been questioned due to the fear of perforation and tumour spread. This study aimed to compare SEMS and stoma as bridge to surgery in acute malignant large bowel obstruction in the Swedish population. Method: Medical records of patients identified via the Swedish Colorectal Cancer Register 2007–2009 were collected and scrutinized. The inclusion criterion was decompression intended as bridge to surgery due to acute malignant large bowel obstruction. Patients who underwent decompression for other causes or had bowel perforation were excluded. Primary endpoints were 5-year overall survival and 3-year disease-free survival. Secondary endpoints were 30-day morbidity and mortality rates. Results: A total of 196 patients fulfilled the inclusion criterion (SEMS, 71, and stoma, 125 patients). There was no significant difference in sex, age, ASA score, TNM stage and adjuvant chemotherapy between the SEMS and stoma groups. No patient was treated with biological agents. Five-year overall survival was comparable in SEMS, 56 per cent (40 patients), and stoma groups, 48 per cent (60 patients), P = 0.260. Likewise, 3-year disease-free survival did not differ statistically significant, SEMS 73 per cent (43 of 59 patients), stoma 65 per cent (62 of 95 patients), P = 0.32. In the SEMS group, 1.4 per cent (one patient) did not fulfil resection surgery compared to 8.8 per cent (11 patients) in the stoma group ( P = 0.040). Postoperative complication and 30-day postoperative mortality rates did not differ, whereas the duration of hospital stay and proportion of permanent stoma were lower in the SEMS group. Conclusion: This nationwide registry-based study showed that long-term survival in patients with either SEMS or stoma as bridge to surgery in acute malignant large bowel obstruction were comparable. SEMS were associated with a lower rate of permanent stoma, higher rate of resection surgery and shorter duration of hospital stay. Abstract : This is a nationwide registry-based study on acute malignant large bowel obstruction comprising 196 cases in which all medical files were scrutinized. The results show that SEMS as bridge to surgery were associated with comparable long-term survival and recurrence rate compared to decompression by stoma, higher rate of fulfilled resection surgery and lower permanent stoma rate.